Clinical application of TICL implantation for ametropia following deep anterior lamellar keratoplasty for keratoconus: A CONSORT-compliant article. Issue 8 (February 2017) - Qin, Qin; Yang, Liping; He, Zifang; Huang, Zhenping
Abstract: Background: This study aimed to investigate the clinical application of phakic toric intraocular collamer lens (TICL) implantation in treating ametropia following deep anterior lamellar keratoplasty (DALK) for patients with keratoconus, especially the effectiveness and safety of high astigmatism and indications of TICL implantation after corneal transplantation. Methods: Using the self-controlled case series observation approach, 9 patients with ametropia (9 eyes) who underwent DALK surgery for keratoconus 1.5 years ago with stitches removed 3 months ago were kept under observation from May 2013 to April 2014 in Ophthalmic Center of Nanjing Drum Tower Hospital affiliated to Nanjing Medical University. TICL implantation was performed in all patients. The uncorrected visual acuity (UCVA) and best-corrected visual acuity (BCVA) were examined before surgery and 1 week, 6 months, 1 year, and 2 years after surgery. Corneal astigmatism, corneal thickness, anterior chamber depth, corneal endothelial cell density (ECD), and preoperative and postoperative intraocular pressures at different time points were measured. Intraoperative or postoperative complications of TICL implantation were observed, and the safety of the operation was evaluated. Results: The UCVA and BCVA in all operated eyes were better 6 months after surgery than before surgery. The spherical diopter and cylindrical diopter decreased to different degrees after surgery. Six months after surgery, the deviation of TICL axis in all operated eyes was less than 10 degrees, tending to be stable. No severe intraoperative or postoperative complication occurred. Conclusion: TICL implantation was an optional choice for ametropia correction after DALK surgery, especially in patients with high astigmatism.